Denominal verbs in Turkish - Gedik, Müge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The aim of this study is to investigate the structural properties of denominal verbs derived with the suffix –lA in Turkish and their implications for the VoiceP-vP split. For this purpose, we first analyze Turkish derived and underived verbs in terms of the Voice-v bundling hypothesis proposed by Pylkkänen (2008). Languages can exhibit bundling or non-bundling patterns for Voice and v (Harley, 2017; Pylkkänen, 2008). Turkish clearly qualifies as a non-bundling language when underived verbs are considered (Key, 2013). In this study, we focus on denominal verbs derived with –lA, and show that a bundling pattern is also available in Turkish, as –lA encompasses properties associated both with VoiceP and vP. Hence, Turkish exhibits both a split pattern in terms of Voice-v bundling with underived lexical verbs, and a bundling pattern with verbs derived with –lA. In order to account for this variation, we suggest that a Nano-syntactic analysis following Ramchand (2008, among others) represents the properties of the verbal domain. We show that the decomposition helps reveal the characteristics of the –lA suffix which can contribute various event and argument structures. We lastly analyze the suffixes –lAn and –lAş and introduce an explication on scalarity properties of degree achievement verbs.
Keywords: Turkish language -- Denominative.; Turkish language -- Verb.